The influence of cultural Intelligence on the relationship between social capital and entrepreneurial performance: a study of foreign traders in Johannesburg’s informal economy - Mtolo, Sabelo Goodman (My University, 2017)
Entrepreneurship continues to dominate public discourse as has been the case for the past century; this topic has been widely discussed in academia and policy development, not only as an abstract concept, but as a necessity to activate economic growth, especially for developing countries such as South Africa. Many authors have argued that the mixture of good entrepreneurial activity in the formal and informal sector is necessary and it is interlinked. As such, the multifaceted nature of entrepreneurship continues to be a subject of contention, especially when it comes to issues surrounding entrepreneurial performance. The purpose of this research was to investigate the influence of Cultural Intelligence on the relationship between Social Capital and Entrepreneurial Performance amongst foreign traders based in Johannesburg’s informal economy. The major studies underlying this research are in agreement in the field of social science and business studies, suggesting that Entrepreneurship is embedded in social contexts and cannot be wholly understood unless one attempts to evaluate the influence of different social phenomena. This study assessed foreign entrepreneurs’ cross-cultural adjustment capabilities, their social networks and how the two influence entrepreneurial performance. This study was motivated by the 2008 and 2015 xenophobic attacks in the informal economy which exposed a need to understand cultural and social capital dynamics that underpin entrepreneurial performance amongst foreign entrepreneurs. The research model for this study sought to investigate the mediating influence of cultural intelligence on the relationship between Social Capital and Entrepreneurial Performance. The results of this study indicate that Cultural Intelligence is no significant mediator between Social Capital and Entrepreneurial Performance amongst foreign traders in the informal economy. The results of this further reflected significant differences in attitudes between the groups of foreign traders under study.
A dissertation submitted to the Faculty of Commerce, Law and Management, at the University of the Witwatersrand, in fulfilment of the requirements of the degree of Master of Commerce in the School of Economic and Business Sciences - Management, Johannesburg, June 27
Keywords: Entrepreneurship--Social aspects--South Africa; Informal sector (Economics)--South Africa; Intercultural communication--South Africa; Social capital (Sociology)